Методика ознайомлення молодших школярів з вишивкою при вивченні технологічної освітньої галузі в початковій школі - Предик, Аліна Анатоліївна (Чернівецький національний університет, імені Юрія Федьковича, 2022)
The article proposes a method of familiarizing younger schoolchildren with embroidery, with peculiar specific features, which necessarily include the following components: the content of the development of the creative abilities of schoolchildren, their interests and hobbies, the rules for observing safety techniques when working with the necessary materials.
Методика ознайомлення молодших школярів з вишивкою при вивченні технологічної освітньої галузі в початковій школі
Keywords: вишивання; українська вишивка; види швів; методика вишивання в початковій школі